Acoustics in nineteenth-century literature and science listening at the threshold - Dickson, Melissa (Cambridge studies in nineteenth-century literature and culture, 2025)
What did it mean to hear, for the first time, what George Eliot described as 'that roar which lies on the other side of silence'? Rapid developments in nineteenth-century acoustic science and communications technologies opened up new worlds beyond the limits of normal audibility for the Victorian public. Weaving together explorations of scientific developments with imaginative cultural, spiritual, and literary responses, this book sets out to explore the burgeoning field of acoustics in the nineteenth century and the new language, structure, and conceptual models it offered to broker the boundaries of the individual self. Ranging from Eliot's Middlemarch to Du Maurier's Trilby, and from Laënnec's work on the stethoscope to experiments on animal audition, inquiries into the unconscious, and spiritualist investigations of the hidden world of vibrations, it demonstrates the profound challenge to the boundaries of the human that was issued by new sound technologies in the Victorian period